Evaluations of N-(Isobutoxymethyl) acrylamide gel dosimeter by NMR technique for radiotherapy and uncertainty in dose measurements. (June 2019) - Basfar, A.A.; Moftah, B.; Lotfy, S.; Al-Moussa, A.A.; Soliman, Yasser S.
Abstract: N -(Isobutoxymethyl) acrylamide (NIBMA) monomer in gelatin, named NIBMAGAT gel dosimeter, was prepared and investigated by nuclear magnetic imaging (NMR) for radiotherapy in the dose range of 0–30 Gy. NIBMA monomer polymerizes upon irradiation, increasing spin–spin relaxation rate R2 . The addition of glycerol as a co-solvent in the gel matrix improved its radiation sensitivity better than the co-solvents of acetone and methanol. The increase of glycerol content by 1% wt/wt enhanced the sensitivity by ˜ 3.1%. This gel has better radiation sensitivity as compared to the polyacrylamide gel (PAG) dosimeter; the sensitivities of NIBMAGAT gel and normoxic polyacrylamide gel (nPAG) are ≈0.13 and ≈0.1 s −1 .Gy −1, respectively. By comparing NIBMAGAT gel dosimeter with PAG, nMAG and nPAG gel dosimeters, NIBMAGAT gel dosimeter is less influenced by scanning temperature than the last three dosimeters. The gel is water equivalent and has an energy-independent response from 80 keV to 20 MeV. The overall uncertainty of dose measurement using NIBMAGAT gel is 5.46% at 2σ. Our findings suggest the applicability of using NIBMAGAT gel dosimeter by NMR technique for dose verification/planning in the practice of clinical radiotherapy. Highlights: N -(Isobutoxymethyl) acrylamide (NIBMA) polymer gel dosimeters were prepared. Glycerol enhances the radiation sensitivity of the gel better than the others do. Radiation sensitivity of NIBMA gel is ˜ 0.13 s −1 .Gy −1 and nPAG is ˜ 0.1 s −1 .Gy −1 . The variation between 7 batches of NIBMA dosimeter is 0.84% at 1σ. The uncertainty of the system in range 0–20 Gy is 5.46 at 2σ, 95% confidence level.